2016
DOI: 10.21009/jppp.051.05
|View full text |Cite
|
Sign up to set email alerts
|

Job Demands Dan Workplace Well-Being Pada Guru Sekolah Luar Biasa Negeri

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
2
7
0
3
Order By: Relevance
“…It related toLove et al (2007) that high job demands tend to trigger low workplace well-being. This is also in line with research conducted byWulan and Putri (2016), which examined the relationship between job demands and workplace well-being in Sekolah Luar Biasa (SLB) teachers. This study showed a significant effect of job demands on workplace well-being in teachers of SLB.…”
supporting
confidence: 88%
“…It related toLove et al (2007) that high job demands tend to trigger low workplace well-being. This is also in line with research conducted byWulan and Putri (2016), which examined the relationship between job demands and workplace well-being in Sekolah Luar Biasa (SLB) teachers. This study showed a significant effect of job demands on workplace well-being in teachers of SLB.…”
supporting
confidence: 88%
“…tuntutan pekerjaan menjadi perawat cukup beresiko dan cenderung menyebabkan stres dalam menjalankan fungsinya. Tinggi atau rendah tuntutan kerja dapat pula meningkatkan atau menurunkan kesejahteraan kerja seseorang (Wulan & Putri, 2016). Bakker, Schaufeli, Demerouti, dan Nachreiner (2001) mendefinisikan tuntutan pekerjaan adalah keadaan pegawai berdasar beban pekerjaan, merujuk pada keadaan fisik, psikologis, sosial atau organisasi dari pekerjaan, memerlukan kemampuan fisik dan psikologis yang berkelanjutan dan dihubungkan dengan resiko tertentu.…”
Section: Pendahuluanunclassified
“…Teachers need welfare to support the implementation of various job demands found in schools. In this case, work demands can create pressures that affect teachers' well-being (Wulan & Putri, 2016). Therefore, researchers currently study a lot about teacher well-being in the workplace by using several terms, including employee and workplace well-being (Burns & Machin, 2012), teacher well-being; Virtanen, Vaaland, & Ertesvåg, 2019;Hwang et al, 2019;Graham & Truscotthttps, 2019;Sasmoko, Herisetyantri, Suroso, & Ying, 2017), Psychological well-being guru (Liang, Peng, Zhao, & Wu, 2017).…”
Section: 10 Introductionmentioning
confidence: 99%